Chromatography Techniques and Their Applications in Environmental Analysis: A Study of Pollutant Detection and Monitoring in Air, Water, and Soil - Kiani, Asna Fatima; Ume Farwa; Malik, Muhammad Raza; Akhtar, Nida (Indus Journal of Bioscience Research, 2024)
This study investigated the levels of pollutants such as volatile organic compounds (VOCs), pesticides, herbicides, and heavy metals in air, water, and soil samples, using advanced chromatographic techniques. Air samples were analyzed via Gas Chromatography-Mass Spectrometry (GC-MS) after thermal desorption, while water and soil samples were assessed using High-Performance Liquid Chromatography (HPLC) and Gas Chromatography (GC) for organic contaminants and heavy metals. The research employed rigorous sampling techniques, including grab and composite methods, and calibration using certified reference materials. Results revealed significant variations in pollutant concentrations across different environmental matrices and sampling sites. Notably, water samples showed elevated pesticide levels, while soil exhibited concerning concentrations of heavy metals like lead and cadmium. Statistical analysis indicated significant differences in pollutant levels across locations, which could pose risks to both human health and ecosystems. The study underscores the importance of continuous monitoring and regulatory oversight to mitigate the environmental and health impacts of these contaminants. The findings suggest that stricter regulations and more sensitive analytical methods are necessary for effective pollution control.